Applying opportunistic observations to model current and future suitability of the Kopet Dagh Mountains for a Near Threatened avian scavenger. Issue 1 (February 2021) - Sheykhi Ilanloo, Sayyad; Khani, Ali; Kafash, Anooshe; Valizadegan, Negin; Ashrafi, Sohrab; Loercher, Franziska; Ebrahimi, Elham; Yousefi, Masoud
Many avian species are in danger of extinction due to anthropogenic activities and climate change. Human activities have led to eradication of many natural habitats and climate change has altered species distribution especially in mountainous habitats. In the present study, we used distribution records of a Near Threatened avian scavenger, bearded vulture ( Gypaetus barbatus ) that were collected through 9 years of opportunistic observations and modeled its distribution in the Khorasane-Razavi Province in Iran. We also assessed the impacts of future climate change on the distribution of this species. Our results show that most suitable habitats for bearded vulture are in the northern regions of the Khorasan-e-Razavi province. The most important variables affecting the distribution of the bearded vulture were the annual precipitation (37.5% contribution), landcover (22% contribution), and distance to road (16.2% contribution). Our results also showed that around 80% to 91% of the species' suitable habitats will decrease due to climate change in the future. Suitable habitats of the species that are predicted to remain suitable in the future should be prioritized for conservation. Human activities like road expansion should be avoided in areas with high suitability for this species. This study stresses the need for action to conserve this vulture in the Khorasan-e-Razavi province, and beyond its borders.